Amine-borane sigma-complexes of rhodium. relevance to the catalytic dehydrogenation of amine-boranes. - Douglas, T; Chaplin, AB; Weller, A (2008)
Rhodium amine-borane sigma-complexes of H3BNHMe2 have been isolated which are potential intermediates in the catalytic dehydrogenation of H3B.NHMe2.